INFLUENCE OF PLASTIC DEFORMATION CARBON STEEL ON THE PROCESS OF BURNING ELECTRIC ARC - Igor Alex VAKULENKO; Sergey PLITCHENKO; Bulent KURT; Hangardas ASKEROV; Svetlana PROYDAK; Ahmet Emrah ERDOGDU (Scientific Journal of Silesian University of Technology. Series Transport)
During a study of the combustion process of a direct polarity electric arc, a directly proportional dependence of the electric current value on the degree of cold plastic deformation of carbon steel used as an electrode was found. To calculate the value of the electric current during arc burning, in the indicated ratio, it was proposed to replace the surface tension force of the liquid metal with the surface tension of ferrite of plastically deformed carbon steel. Calculation of the ferrite’s surface tension value on the deformation degree of the steel under study through the size of the coherent scattering regions was used to explain the observed dependence of the electric current during arc burning. From the analysis of the considered correlation ratios, it was found that with an increase in the cold deformation degree, the refinement of the coherent scattering regions results in the ferrite’s surface tension increase and consequently, to an increase in the electric current during arc burning. Comparative analysis of the obtained results of calculating the value of electric current during arc burning through the surface tension of ferrite of cold-deformed carbon steel showed a fairly good coincidence with experimental data. The differences did not exceed 9%.